2014
DOI: 10.4317/jced.51324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographical evaluation of the healing of large periapical lesions using triple antibiotic paste, photo activated disinfection and calcium hydroxide when used as root canal disinfectant

Abstract: Objectives: To evaluate clinically and radio graphically, the healing following nonsurgical treatment of periapical lesions when Photo Activated Disinfection(PAD), triple antibiotic paste and calcium hydroxide was used as root canal disinfectant. Material and Methods: Sixty patients (20 for PAD, 20 for triple antibiotic paste, 20 for calcium hydroxide) with periapical lesions in the maxillary and mandibular anterior region were selected from the outpatient section of the Department of Conservative Dentistry &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In the present study, triple antibiotic paste showed a considerable decrease in microbial pathogens from root canal of the sample teeth, the results of the present study were concordance with various studies conducted in the past. [121314171819] In a study conducted on dog teeth (immature) affected with apical periodontitis by Windley et al [19] shows a considerable decrease in bacterial pathogen from root canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, triple antibiotic paste showed a considerable decrease in microbial pathogens from root canal of the sample teeth, the results of the present study were concordance with various studies conducted in the past. [121314171819] In a study conducted on dog teeth (immature) affected with apical periodontitis by Windley et al [19] shows a considerable decrease in bacterial pathogen from root canal.…”
Section: Discussionmentioning
confidence: 99%
“…[11] The use of these antibiotics as intracanal medicament also been explored in various studies. [12131415] In the Indian scenario, there are no studies done which could explore the use of these antibiotics in combination as an irrigating solution except or one study where few of these antibiotics were used as an irrigant solution. [16] The combination of various antibiotics such as ciprofloxacin, metronidazole, and tetracycline and its use and efficacy has not yet been researched yet.…”
Section: Introductionmentioning
confidence: 99%
“…In another long follow-up study, Johns et al observed the clinical and radiographic evolution of the healing of large periapical lesions following three treatments, namely aPDT, triple antibiotic paste, and calcium hydroxide. In their conclusions, the authors report that aPDT was a more effective intracanal disinfectant at 6-, 12-, and 18-month follow-up (Johns et al, 2014). All these studies together indicate the effectiveness of aPDT in improving endodontic therapy success rates and should be pursued in future studies.…”
Section: Antimicrobial Photodynamic Therapy Applications In Endodonmentioning
confidence: 85%
“…There are supplementary procedures that may probably enhance periapical lesion healing, such as: using a triple antibiotic paste (Hoshino paste containing Ciprofloxacin 500 mg, Metronidazole 400 mg, and Minocycline 100 mg) as a canal dressing, photo-activated disinfection (PAD) or magnetostimulation. However, there is still a need for further study in order to confirm their abilities [ 8 , 9 ]. RCT with a mineral trioxide aggregate (MTA) as an apical closure can be used for the apexification of an immature tooth with a large periapical lesion [ 10 ].…”
Section: Introductionmentioning
confidence: 99%